OsMFT2 is involved in the regulation of ABA signaling‐mediated seed germination through interacting with OsbZIP23/66/72 in rice. (14th April 2020) - Song, Song; Wang, Guanfeng; Wu, Hong; Fan, Xiaowei; Liang, Liwen; Zhao, Hu; Li, Shuangle; Hu, Yong; Liu, Haiyang; Ayaad, Mohammed; Xing, Yongzhong
Summary: Seed germination is a complex process involving various physical and biochemical cues, determined by exogenous and endogenous factors. Here, we identified a gene, OsMFT2, that negatively regulates seed germination in rice. OsMFT2 knock‐out lines exhibited pre‐harvest sprouting, whereas OsMFT2 overexpression lines showed delayed germination. RNA expression profiling showed that OsMFT2 was specifically expressed in seeds. Subcellular localization indicated that OsMFT2 was a nuclear protein. Exogenous abscisic acid (ABA) treatment of imbibed seeds and seedlings indicated that OsMFT2 altered ABA sensitivity during seed germination and post‐germination growth. In vivo and in vitro assays showed that three bZIP transcription factors, OsbZIP23, OsbZIP66 and OsbZIP72, interacted with OsMFT2. OsbZIP23/66/72 bound to the promoter of Rab16A, a typical gene containing the ABA‐responsive element, and OsMFT2 enhanced the binding to the Rab16A promoter. Moreover, several ABA‐responsive genes were differentially expressed in the imbibed seeds of OsMFT2 transgenic lines and the wild type. The performance of the transgenic plants demonstrated that overexpressing OsbZIP23 rescued the pre‐harvest sprouting phenotype and the decrease in ABA‐signaling genes expression caused by OsMFT2 knock‐out. All of these results demonstrate that OsMFT2 positively regulates ABA‐responsive genes through interacting with OsbZIP23/66/72 and functions in seed germination. Significance Statement: Our findings revealed a novel gene responsible for the regulation of seed germination and established a relationship between OsMFT2 and ABA signaling. These findings enrich our knowledge concerning the regulatory network of seed germination and ABA signaling in rice and provide new insights for understanding the role of PEBP proteins, which act as transcription co‐factors.